Erased Yet Central: Female Representation in Purna Bahadur Ko Sarangi - Sharma, Bimala (Humanities and Social Sciences Journal, 2024)
This research paper critically investigates the representation of women primarily concentrating on the character of Batuli in the Nepali film “Purna Bahadur Ko Sarangi.” Studying the film from gender perspective employing feminist film theory, the article interrogates the methods in which Batuli’s presence, actions, dialogues and eventual erasure is systematically performed which replicates wider societal attitudes towards women who challenge conventional societal norms. In spite of Batuli’s decisive role in sparking the transformation in her family, she is systematically erased from the canvas of the film, resonating the true-to-life marginalization of women’s contributions reflecting broader patriarchal structures embedded in both cinematic and societal frameworks. By positioning the film, in both Nepali cultural context and feminist film theory, this research accentuates the necessity of re-evaluating representation of women in contemporary cinema. The paper seeks to answer: how Batuli is represented in Purna Bahadur Ko Sarangi and why is she simultaneously erased on screen and still central in narrative function? It employs a qualitative methodology analyzing the content of the film which is grounded on Laura Mulvey’s feminist film theory of the male gaze and visual semiotics. E. Ann Kaplan’s work on the female image in patriarchal cinema, and Stuart Hall’s concept of representation. The main focus is on dialogue, cinematography, and narrative structure to grasp the symbolic positioning of women. All this assist a critical study of how women characters are represented and function within the cinema.